Post-Migration Education Among Refugees in the Netherlands - van Tubergen, Frank (Frontiers in Sociology, 2022)
Refugees face significant barriers in the labor markets of western countries due to limited transferability of educational credentials. Post-migration education can increase refugees’ chances in the labor market, but little is known about the prevalence and underlying patterns of such post-secondary educational investments. I contribute to the literature by analyzing survey data from the Netherlands on post-migration education among more than 3,000 adult refugees who come from Afghanistan, Iran, Iraq, former Yugoslavia, and Somalia. I find that refugees’ investments in schooling depend on both pre- and post-migration characteristics. Results show that post-migration schooling is more common among adult refugees who are higher educated, who arrived at a younger age, who have applied for recognition of their foreign education, and who have (successfully) participated in integration and/or language courses. When refugees are kept in an asylum center for a longer time, they are less likely to invest in post-migration education.